Some new paranormed sequence spaces defined by Euler and difference operators - Karakaya, V.; Polat, H. (My University, 2010)
The spaces ?co(p), ?c(p) and ? linfin(p) were defined by Ahmad and Mursaleen [1]. In [2], Altay and Polat also defined the sequence spaces er0(?), er c(?) and er?(?), and determined the absolute Köthe-Toeplitz duals of these spaces. The main purpose of this work is to introduce some new paranormed sequence spaces defined by Euler and difference operators and to compute their ?-, ?-, ?-duals. Also some of the matrix transformations has been characterized. All rights reserved © Bolyai Institute, University of Szeged.
Keywords: Euler and difference sequence spaces; Köthe-toeplitz duals; Matrix mapping; Paranormed sequence space